If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -10 + 6 = 2(ky + -1) + -1y Reorder the terms: -10 + 6 + 15y = 2(ky + -1) + -1y Combine like terms: -10 + 6 = -4 -4 + 15y = 2(ky + -1) + -1y Reorder the terms: -4 + 15y = 2(-1 + ky) + -1y -4 + 15y = (-1 * 2 + ky * 2) + -1y -4 + 15y = (-2 + 2ky) + -1y Solving -4 + 15y = -2 + 2ky + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2ky' to each side of the equation. -4 + -2ky + 15y = -2 + 2ky + -2ky + -1y Combine like terms: 2ky + -2ky = 0 -4 + -2ky + 15y = -2 + 0 + -1y -4 + -2ky + 15y = -2 + -1y Add 'y' to each side of the equation. -4 + -2ky + 15y + y = -2 + -1y + y Combine like terms: 15y + y = 16y -4 + -2ky + 16y = -2 + -1y + y Combine like terms: -1y + y = 0 -4 + -2ky + 16y = -2 + 0 -4 + -2ky + 16y = -2 Add '4' to each side of the equation. -4 + -2ky + 4 + 16y = -2 + 4 Reorder the terms: -4 + 4 + -2ky + 16y = -2 + 4 Combine like terms: -4 + 4 = 0 0 + -2ky + 16y = -2 + 4 -2ky + 16y = -2 + 4 Combine like terms: -2 + 4 = 2 -2ky + 16y = 2 Reorder the terms: -2 + -2ky + 16y = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -2ky + 16y = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-1 + -1ky + 8y) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + -1ky + 8y)' equal to zero and attempt to solve: Simplifying -1 + -1ky + 8y = 0 Solving -1 + -1ky + 8y = 0 Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -1ky + 1 + 8y = 0 + 1 Reorder the terms: -1 + 1 + -1ky + 8y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1ky + 8y = 0 + 1 -1ky + 8y = 0 + 1 Combine like terms: 0 + 1 = 1 -1ky + 8y = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| X^2-11x=-56 | | (0)=-4.8x+1.2 | | (2.5b-9)+6b=-7 | | 8m-6=2 | | 5(a-1)=5 | | 5(3x+-2)=4+-6x | | 4(3x+-2)=4+-6x | | -11=7+b | | 4w+10=90 | | 43v-6=8+23v | | 12x+6=5y+10 | | 4w+10= | | 2x-3(3-7)+3= | | 3(3x+-2)=4+-6x | | Y=-4.8(0)+1.2 | | 2(3x+-2)=4+-6x | | 150m-125m+38200=40400-175m | | 6m-2=m+3 | | (54b-27ab)= | | 2x^2-20=8 | | 3n+8=92 | | 20y=25y^2 | | 5x-11=8x+12 | | 4x-20.65=6.7 | | 3x+y=7xy | | 0.5x+0.1*5x=62.15 | | X^2=11x-56 | | 0.5x+0.1(5x)=62.15 | | 4x-20.65=20.1 | | -6f-9f=15 | | 15c+1c+21c= | | 61h=9.3-3.2h |